2022
DOI: 10.3390/ijerph19010537
|View full text |Cite
|
Sign up to set email alerts
|

Relations among Pro-Environmental Behavior, Environmental Knowledge, Environmental Perception, and Post-Materialistic Values in China

Abstract: During the economic boom, China’s government was mainly concerned with economic development; however, numerous environmental problems have arisen. Evidence suggests that Chinese individuals’ pro-environmental behavior (PEB) is at a low level in Asia. However, it does not match their high-quality environmental knowledge. In this paper, the database of the Chinese General Social Survey was used to explore the correlation between environmental knowledge and PEB in a broader context. Subsequently, environmental pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…The influencing factors at the micro level are mostly concentrated on environmental knowledge [9,[28][29][30], environmental perception [7,9,31,32], environmental protection attitudes [31,33,34], theory of planned behavior (TPB) [35][36][37] and personal habits [37].…”
Section: Influencing Factors Of Peb At the Micro Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…The influencing factors at the micro level are mostly concentrated on environmental knowledge [9,[28][29][30], environmental perception [7,9,31,32], environmental protection attitudes [31,33,34], theory of planned behavior (TPB) [35][36][37] and personal habits [37].…”
Section: Influencing Factors Of Peb At the Micro Levelmentioning
confidence: 99%
“…Furthermore, research has shown that the association between environmental knowledge and PEB is substantially more robust in private environmental behaviors than in their public counterparts [28]. Residents' perceptions of sustainability-related climate directly impact on their participation in PEB [9]. In particular, the positive thoughts of homemakers about perceived behavioral control have a positive effect on guiding their recycling behaviors [32].…”
Section: Influencing Factors Of Peb At the Micro Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the students' subjective norm and perceived behavioural control are positively and significantly associated with their PEIs. Recently, in China, during the economic boom period, environmental perception has a partial mediating role between environmental knowledge and PEB (Xie and Lu, 2022). Similarly, the factors such as awareness, attitudes and norms are robust predictors of intention to engage in post-consumer plastic packaging activity (Widayat et al, 2022).…”
Section: Literature Review and Conceptualizationmentioning
confidence: 99%
“…Environmental knowledge directly promotes environmental behavior [ 22 ], or indirectly drives behavior through environmental attitudes and behavioral intentions [ 23 ]. For a specific country, the relevance between environmental knowledge and environmental behavior might change with individual demographic characteristics [ 24 ]. Based on this, the H1 hypothesis is proposed:…”
Section: Introductionmentioning
confidence: 99%